DEVELOPMENT OF TOURISM TRAVEL PATTERNS IN LAU BAGOT TOURISM VILLAGE DAIRI DISTRICT - Rosdiana Pakpahan (LPPM Institut Pendidikan Nusantara Global, 2023)
One place that has great tourism potential is the Dairi district. Just like other regions in North Sumatra, Dairi Regency has many tourist destinations that have the potential to be big enough to attract tourists. Lau Bagot Tourism Village is one of the leading tourist villages in Dairi Regency. Data collection techniques used to obtain data include interviews, observations, literature studies, and documentation studies. As well as conducting in-depth interviews, this study included the following participants: the head of the Lau Bagot Tourism Village Pokdarwis, the head of Lau Bagot Village, Hamlet Head, and members of the Lau Bagot Tourism Village Pokdarwis. Data analysis techniques used in this study were qualitative. The single point and chaining loop travel patterns are travel schemes that are well implemented in Lau Bagot Tourism Village because in the single point travel pattern, the willingness is in the form of road access that only has one lane so that the departure and return routes will follow the same route. Whereas in the chaining loop pattern on other routes, when going to travel between tourist attractions, the paths that are passed back are not the same, so they don't go through the same route, so the travel pattern is in the form of a chaining loop.